Charles Pinkerton collection of Arthur and Herndon family papers - Pinkerton, Charles, -1974.
Correspondence, genealogical material, notes, press clippings, and other papers relating to Pinkerton's father-in-law, Chester Alan Arthur; Arthur's father, William Arthur, and father-in-law and explorer, William Lewis Herndon; and other members of the Arthur and Herndon families. Includes volume of letterpress copies of telegrams (1883 January 15-December 1) received by Chester Alan Arthur and notes made by Arthur's biographer, Thomas C. Reeves.
Son-in-law of U.S. president Chester Alan Arthur.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886.; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Arthur, William, -- 1796-1875.; Herndon, William Lewis, -- 1813-1857.; Reeves, Thomas C., -- 1936-; Arthur family; Herndon family; United States -- Politics and government -- 1881-1885.; Collectors